2020
DOI: 10.21608/javs.2020.97600
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Hematobiochemical And Trace-Elements Alterations In Camels With Sarcoptic Mange (Sarcoptes Scabiei Var Cameli) Accompanied By Secondary Pyoderma

Abstract: Sarcoptic mange is a common, zoonotic and important disease facing camel farming systems with grave economic losses. The present study was applied to estimate the effect of sarcoptic mange on clinical condition, hematobiochemical criteria and trace-element status among camels in Egypt. A total number of thirty dromedary camels (Camelus dromedarius) were investigated in the present study. The animals were divided into fourteen diseased camels affected with sarcoptic mange and sixteen apparently healthy camels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The changes in blood copper values linked to health status could occur mainly because of the inflammation process, which provokes hypercupremia, as observed in other species. However, this aspect was not investigated in camels, and in reverse a decrease in the copper concentration in the blood was reported in cases of testicular degenerative injury [ 95 ], anemic camels [ 96 ] or mange [ 97 ], but no effect of mastitis or internal parasites was revealed [ 98 , 99 ]. In camels hospitalized in several vet clinics from Egypt, Hassan et al [ 100 ] did not find any difference between healthy and sick camels, regardless of the disease (respectively 92.7 ± 2.5 and 92.9 ± 0.5 µg/100 mL).…”
Section: Trace Mineral Status In Camel Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in blood copper values linked to health status could occur mainly because of the inflammation process, which provokes hypercupremia, as observed in other species. However, this aspect was not investigated in camels, and in reverse a decrease in the copper concentration in the blood was reported in cases of testicular degenerative injury [ 95 ], anemic camels [ 96 ] or mange [ 97 ], but no effect of mastitis or internal parasites was revealed [ 98 , 99 ]. In camels hospitalized in several vet clinics from Egypt, Hassan et al [ 100 ] did not find any difference between healthy and sick camels, regardless of the disease (respectively 92.7 ± 2.5 and 92.9 ± 0.5 µg/100 mL).…”
Section: Trace Mineral Status In Camel Bloodmentioning
confidence: 99%
“…Indeed, some studies in Morocco [ 124 ], China [ 25 ], the UAE [ 125 , 126 ], Sudan [ 61 ] and Saudi Arabia [ 127 ] reported such mean values. However, lower concentrations of between 25 and 53 ng/mL were found by Abdelrahim [ 128 ] in Sudan, 21 ng/mL being found by Bengoumi et al [ 129 ] in Morocco, 12.6 ng/mL by Nafizi et al [ 130 ] in Iran and 50 ng/100 mL in healthy camels from Egypt [ 97 ]. On the other hand, higher concentrations were recorded by other authors, with 274 to 288 ng/mL being found in Chinese Bactrian camels [ 131 ] and 200 ± 90 ng/mL in dromedaries from the UAE [ 61 ].…”
Section: Trace Mineral Status In Camel Bloodmentioning
confidence: 99%
“…This is also an important factor in the death of infected animals that died in winter and early spring. Additionally, breaks in the epidermis allow the development of pathogenic bacterial infection (Abdel-Saeed, 2020;Romani et al, 2015). In humans, crusting is a rare manifestation of scabies, caused by the uncontrolled proliferation of mites in the skin as a result of an insufficient immune response by the host (Karthikeyan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Documented changes included reduced bacterial diversity and a higher abundance of Staphylococcus spp. and Corynebacterium in mange-affected individuals, which has been proposed to be due to excretions from the mite that inhibits the complement activation pathways [ 18 ] and the bacteria speculated to be the leading cause of secondary infections in multiple hosts [ 19 21 ]. However, it is unclear how consistent mange-microbiota relationships may be across other host taxa and geographic regions or whether inter-species and biotic/abiotic environmental differences might influence changes in microbiota.…”
Section: Introductionmentioning
confidence: 99%